Idiopathic Spinal Cord Herniation Associated With a Thoracic Disc Herniation: Case Report, Surgical Video, and Literature Review. Issue 6 (July 2020) - Randhawa, Pal S.; Roark, Christopher; Case, David; Seinfeld, Joshua
Abstract : Purpose: The aim of this publication is to present a case of idiopathic spinal cord herniation (ISCH) associated with a transdural disk herniation, demonstrate an operative technique used to treat this condition and provide an updated review the literature. Background Context: ISCH is an infrequent condition that can cause progressive myelopathy leading to severe neurological dysfunction. This condition is characterized by ventral displacement of the spinal cord across a defect in the dura, either congenital or acquired, resulting in vascular compromise and adhesion that subsequently causes injury to the spinal cord. We present the management of such a patient, in addition to a review of the literature regarding management of ISCH. Methods: This patient underwent surgery using the dural graft sling technique for repair of the dural defect and restoration of normal spinal cord position within the thecal sac. A review of the literature revealed a total of 171 patients supplemented by our 1 patient, which were then analyzed. Results: The majority of patients, treated with a variety of surgical techniques, experienced improvements in symptomatology. Our patient experienced significant improvement in symptomatology. Conclusions: Although ISCH is a rare clinical condition that causes myelopathy, patients managed with surgery generally, though not universally, have a favorable neurological outcome. The associated surgical technique video demonstrates the dural sling technique for the treatment of this rare disorder. Abstract : Supplemental Digital Content is available in the text.